Successful surgical treatment of a four part fracture dislocations of the proximal humerus and coracoid avulsion - Gazzotti, Gabriele; Patrizio, Luigi; Bondioli, Stefania; Scaravella, Edoardo; Sabetta, Ettore (Acta Biomedica Atenei Parmensis, 2015)
racture-dislocation of the proximal humerus (usually occurring after violent trauma) may be more frequently associated with a poor long-term results because the destruction of the hinged periosteum is associated with an high-risk of avascular necrosis of the head of the humerus (1, 2). Concomitant coracoid fracture with anterior shoulder dislocation in such case is something extremely rarely reported (8). Herein, we describe a challenging case of a 44 years old man with 4-parts fracture of the right proximal humerus, dislocation of the glenohumeral joint associated with coracoid avulsion. Considering the severe functional damage on the right shoulder, the patient was immediately treated with open reduction internal fixation (ORIF) at the level of the proximal humerus and with the concomitant placement of one screw at the level of coracoid avulsion. At a 15 months follow up we observed an excellent clinical and radiographic results. We take the opportunity of this unusual case for briefly discuss on such clinical condition and surgical options. (www.actabiomedica.it)